2017
DOI: 10.1002/int.21948
|View full text |Cite
|
Sign up to set email alerts
|

On the use of convolutional neural networks for robust classification of multiple fingerprint captures

Abstract: Fingerprint classification is one of the most common approaches to accelerate the identification in large databases of fingerprints. Fingerprints are grouped into disjoint classes, so that an input fingerprint is compared only with those belonging to the predicted class, reducing the penetration rate of the search. The classification procedure usually starts by the extraction of features from the fingerprint image, frequently based on visual characteristics. In this work, we propose an approach to fingerprint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 63 publications
(138 reference statements)
2
52
0
Order By: Relevance
“…The set of valid transformations that improves the performance of the CNN-model depends on the particularities of the problem. Several previous studies have demonstrated that increasing the size of the training dataset using different data-augmentation techniques increases performance and makes the learning of CNNs models robust to changes in scales, brightness and geometrical distortions [44,47].…”
Section: Training Phase: Cnn-classifier With Fine-tuning and Data Augmentioning
confidence: 99%
“…The set of valid transformations that improves the performance of the CNN-model depends on the particularities of the problem. Several previous studies have demonstrated that increasing the size of the training dataset using different data-augmentation techniques increases performance and makes the learning of CNNs models robust to changes in scales, brightness and geometrical distortions [44,47].…”
Section: Training Phase: Cnn-classifier With Fine-tuning and Data Augmentioning
confidence: 99%
“…Contrary to the statistical and model‐based practices, ANNs are self‐adaptive in inferring underlying functional associations from the input data . Several nonlinear hidden layers between input and output modules are introduced, supporting the system to learn complex functions and features, for better predictions …”
Section: Predicting Withdrawals In Vlementioning
confidence: 99%
“…A larger dataset could be constructed from a small number of initial samples with data argumentation. Using different data argumentation methods to increase the size of the training dataset increased the generalisation performance of the model, reduced the risk of overfitting, and made the CNN model more robust to the scale, brightness, and geometric distortions [28,29].…”
Section: Data Samplingmentioning
confidence: 99%